LITERASI EKONOMI SYARIAH PADA ANAK DAN REMAJA DALAM MENGHADAPI PRAKTIK JUAL BELI ONLINE DI ERA DIGITAL - Zairah (LPPM IAD Probolinggo, 2026)
The rapid development of digital technology has increased children's and adolescents' involvement in online buying and selling activities. This phenomenon offers various opportunities while also exposing young users to risks such as consumerism, digital fraud, and participation in transactions that are not in accordance with Islamic principles. This study aims to analyze the importance of Islamic economic literacy for children and adolescents in dealing with online commerce practices in the digital era and to identify educational values that can foster consumption behavior aligned with Islamic teachings. This research employed a qualitative approach using a library research method. Data were collected from scholarly journals, Islamic economics literature, child education studies, digital literacy sources, and fiqh muamalah references, and were analyzed through content analysis techniques. The findings reveal that e-commerce transactions are generally permissible in Islamic law through the application of contracts such as salam, istisna’, and wakalah. However, several digital transaction features, including interest-based PayLater services, mystery boxes, and fake reviews, contain elements of riba, gharar, and tadlis, which are prohibited in Islamic law. Therefore, strengthening Islamic economic literacy from an early age through the cultivation of trustworthiness, honesty, responsibility, justice, and halal consumption values is essential for developing digitally literate, critical, and morally responsible young generations.